Strategy For Improving Community Services Regarding Public Services In Lambangsari Village Government Based On Minimum Service Standards And Service Quality - Helmy, Moehammad Shadiq; Naufalia, Viani; Wilandari, Angestika; Windasari, Vicky (ProBisnis : Jurnal Manajemen, 2023)
This research aims to explore and analyze strategies that can be adopted by the Lambangsari Village Government, Tambun Selatan District, and Bekasi Regency, which is only 21 km from the center of Jakarta City. This research aims to respond to the need for equitable public services throughout the region, especially in villages in the middle of urban areas with intense interaction with the city center. This research also aims to identify specific problems in public services in Lambangsari Village and explore strategies that can be implemented to improve the quality of services to residents. This research design will use the Service Quality approach as the main conceptual framework. The research methodology will include an analysis of tiered service structures from the national to village level, focusing on applying theory and practice contained in the Regulation of the Minister of State Apparatus. This approach will help evaluate the effectiveness of public services at the village level, focusing on factors that influence the successful implementation of service strategies. The findings from this research will provide in-depth insight into the success or failure of the service strategy implemented by the Lambangsari Village Government. These findings can involve operational efficiency, responsiveness to residents' needs, and community satisfaction with village services. Limitations of this research include limited resources, time, and the complexity of local community dynamics.